Does size matter in determining the performance of manufacturing industries? - Aba Ibrahim, Nurhani (2007)
This paper examines the effect of size on the performance of industries within the economy. In a panel setting, it applies the augmented Cobb-Douglas model used by Mankiw et al. (1992) on 73 manufacturing industries in Malaysia for the period 1981-1999. Fixed effect is applied to levels and first difference data. Different proxies for size are used to see if it makes a significant difference to the results. Results show that: (1) annual sales turnover is a better measure for size because it is not biased to capital intensive and labour intensive industries, (2) only the medium and large industries are found to have cyclical pattern, and (3) the change in the size of the large industries seems to be able to explain more of the variations in output per labour compared to the medium and small ones.